ANALYSIS AND CLASSIFICATION OF PAP SMEAR CELLS USING SHAPE FEATURES - JOHARRY, SITI HAJAR (IRC, 2016)
Cervical cancer is known as the most deadly cancer in the world for women and the most preventable ones. High rises of cervical cancer therefore has increased the progressing of research and studies in the medical field. Generally, the cervical cancer grows slowly and is usually easily diagnosed at an early stage where chances to cure is significantly high. Prevention is the key to survive cervical cancer and by prevention is to have the screening process via Pap smear test and this is done by cytotechnologists manually. Be that as it may, this test could take too much of a time and is exposed to such errors that are caused by the observers during the test.